Interventions with Positive Side-Effects: COVID-19 Non-Pharmaceutical Interventions and Infectious Diseases in Europe - Micha Kaiser; Steffen Otterbach; Alfonso Sousa-Poza; David E. Bloom (Institute of Labor Economics (IZA), 2020)
To assess the efficacy of Covid-19 non-pharmaceutical interventions (NPIs) on infectious disease containment in Europe, we first use weekly 2015-20 data on the spread of influenza and respiratory syncytial virus (RSV) to compare the 2019-20 season of these diseases with the previous five. Although the magnitude of results differs between countries, we document much stronger end-of-season declines in infections in the most recent outbreak than in the earlier ones, implying that they may be driven by NPIs implemented in 2020 to combat Covid-19. To test this conjecture, we use detailed country-specific weekly information on Covid-19 NPIs to estimate several panel models that relate NPI implementation to disease incidence across countries. Not only do certain measures significantly reduce the spread of Covid-19, they also curtail the spread of influenza and RSV. Nonetheless, although we identify workplace closures as a particularly effective measure, we find no evidence for the efficacy of other NPIs such as travel restrictions.
Keywords: H30; H23; H12; I18; 330; non-pharmaceutical interventions; infectious diseases; Europe; COVID-19